Legal Protection for Creditors as Holders of Fiduciary Rights Against Unlawful Transfer of Motor Vehicles by Debtors in Financing Agreements - Simangunsong, Daniel P; Setiono, Joko; Rudhanto, Albertus Wahyu (Greenation Publisher & Yayasan Global Resarch National, 2025)
Motor vehicle financing agreements with fiduciary guarantees are a common practice in consumer financing in Indonesia. In practice, debtors often transfer the fiduciary object, such as a motor vehicle, to a third party without the written consent of the creditor, which is contrary to the provisions of Article 23(2) of Law No. 42 of 1999 on Fiduciary Security. Such actions not only violate the agreed-upon agreement but also constitute unlawful acts and may even be classified as criminal embezzlement as stipulated in Article 36 of the Fiduciary Law and Article 372 of the Criminal Code. This study aims to analyze the forms of unlawful transfers, the legal consequences for the debtor, and the legal protections available to the creditor as the holder of the fiduciary right. The methodological approach used is a normative legal analysis, with primary and secondary legal sources including legislation, doctrine, and court rulings. The analysis indicates that legal protection is available both preventively through fiduciary registration and contract clauses, and repressively through civil lawsuits and criminal reports. However, the implementation of legal protection still faces obstacles, including weak law enforcement, low legal literacy among the public, and the suboptimal role of law enforcement officials. Therefore, efforts are needed to enhance the effectiveness of legal protection through regulatory updates and legal education for the public to prevent further violations of fiduciary collateral.